Nivolumab plus ipilimumab in metastatic uveal melanoma: a real-life, retrospective cohort of 47 patients. (31st December 2022) - Salaün, Hélène; de Koning, Leanne; Saint-Ghislain, Mathilde; Servois, Vincent; Ramtohul, Toulsie; Garcia, Agathe; Matet, Alexandre; Cassoux, Nathalie; Mariani, Pascale; Piperno-Neumann, Sophie; Rodrigues, Manuel
ABSTRACT: Although combined PD-1/CTLA-4 inhibition showed limited efficacy in single-arm, phase II trials in metastatic uveal melanoma (mUM), such combination appears frequently used in mUM patients. We here report our experience with nivolumab/ipilimumab in mUM. A retrospective cohort of 47 mUM patients, 24 men and 23 women, received nivolumab/ipilimumab between October 2019 and December 2021, mostly first line (94%). Two regimens were used: nivolumab 1 mg/kg + ipilimumab 3 mg/kg (nivo1ipi3, 49% of patients) and nivolumab 3 mg/kg + ipilimumab 1 mg/kg (nivo3ipi1, 51% of patients). Median follow-up was 37 and 88 weeks in nivo3ipi1 and nivo1ipi3 cohorts, respectively. We observed partial response in two patients (4%) and stable disease in 14 patients (30%), with no significant difference between the two regimens. Median progression-free survival was 13.6 weeks and 11.9 weeks in the nivo1ipi3 and nivo3ipi1 cohorts, respectively ( p = 0.49). Severe adverse events (grade 3 or 4) were observed in seven patients (15%) among which five treated with nivo1ipi3 (22%) and two treated with nivo3ipi1 (8%). These data suggest that nivolumab/ipilimumab combination does not improve clinical outcomes compared to other therapies but is more toxic. In the absence of controlled clinical trials, we would not recommend this combination as a standard treatment in all mUM patients but rather as an option. Patients for whom the benefit–risk ratio could justify the combination need to be defined.